1994
DOI: 10.1073/pnas.91.13.6088
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy of murine teratocarcinoma: separate functions for insulin-like growth factors I and II in immunogenicity and differentiation.

Abstract: Teratocarcinoma is a germ-line carcinoma giving rise to an embryoid tumor with structures derived from the three embryonic layers: mesoderm, endoderm, and ectoderm. Teratocarcinoma is widely used as an in vitro model system to study regulation of cell determination and differentiation during mammalian embryogenesis. Murine embryonic carcinoma (EC) PCC3 cells express insulin-like growth factor I (IGF-I) and its receptor, while all derivative tumor structures express IGF-I and IGF-II and their receptors. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…In addition, this treatment abolished tumorigenicity in syngeneic animals. [5][6][7][8][9][10][11][12] Immunization with the IGF-1 antisense transfectants elicited effective antitumoral immune responses that were both preventive and curative. 7,8 More recently, similar results have been reported by several groups, demonstrating that blockage of IGF-1 receptor with an antisense approach could convert tumor cells to an immunogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this treatment abolished tumorigenicity in syngeneic animals. [5][6][7][8][9][10][11][12] Immunization with the IGF-1 antisense transfectants elicited effective antitumoral immune responses that were both preventive and curative. 7,8 More recently, similar results have been reported by several groups, demonstrating that blockage of IGF-1 receptor with an antisense approach could convert tumor cells to an immunogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further support those obtained in studies of glioblastoma, melanoma, and hepatoma, which indicated that tumor cells transfected either with the IGF-1 antisense or with the B7 gene can directly stimulate naive T cells without the participation of CD4 ϩ T cells. 6,8,14,17 The tumor-specific antitumoral immunity can be adoptively transferred into naive animals by i.v. injection of CTLs generated either in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All mutants were sequence-verified. To express CFTR in PANC-1 epithelia, WT and ⌬6 CFTR were subcloned into the pMT/EP episomal expression cassette, provided by Dr. J. Ilan (37). CFTR-GFP fusion was constructed by shuttling the HpaI/SalI fragment of the pEGFP-N3 vector (BD Biosciences) into pNUT-CFTR-HAC t after eliminating the hemagglutinin (HA) tag.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, overexpression of Akt inhibits apoptosis induced by various stimuli (Yuan et al, 2000). Secondly, treatment of tumour with antibody or anti-sense oligonucleotides targeting IGF-1R could decrease Akt protein expression and sensitize cells to drug-or irradiated-induced programmed cell death (Trojan et al, 1994;Shevelev et al, 1997;and Scotlandi et al, 1998). Finally, our results from kinetics experiments showed that the levels and tyrosine activity of Akt1 were decreased before MCF-7 apoptotic cell death induced the by IGF-1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%